Research and practice of centralized cloud-enabled service provisioning and activation system of PON - Yanbin SHI; Qi YU; Gengshu SU; Yijie JIANG (Dianxin kexue)
The business and technical challenges of provisioning and activation of optical network were elaborated.Design idea of centralized，cloud-enabled and extraction of IOE was proposed.The architecture of“platform+application”provisioning and activation of optical network was constructed.The key technical points like unified data model，distributed data storage，services，open architecture，interactive “message+data”interfaces，distributed process engine，explicited rules management，centralized configuration management under architecture of optical network were given.